Differences between Green Homebuilders and Traditional Homebuilders - Randall A. Cantrell (EDIS)
Homebuilders are not a homogeneous group. Throughout the majority of the US homebuilding history, homebuilders may have used similar practices and building materials, but homebuilders who build to a "green" standard differ from those who do not. This 3-page fact sheet was written by Randall A. Cantrell, and published by the UF Department of Family, Youth and Community Sciences, March 2012.